Metareflections on macroeconomics and macroeconomic policy - Dzionek-Kozłowska, Joanna (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
Book review: Tomasz Kwarciński, Agnieszka Wincewicz-Price (red.), Metaekonomia II. Zagadnienia z filozofii makroekonomii, Kraków, Copernicus Center Press 2019.
Keywords: macroeconomics; macroeconomic policy; metaeconomics